Оптимальне технічне обслуговування відновленої системи із навантаженим резервуванням з урахуванням напрацювання кожного елемента - Peschanskii, O. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
A semi-markov model of maintenance of a parallel structure has been constructed taking into account the total prefailure operation time of each element. Stationary indeces of the system operation quality have been found. Optimal values of the operation time for the elements have been determined for preventive maintenance.